Towards the Knowledge Management: Improving The Role of Organizational Citizenship Behavior Through the Job Satisfaction - Perkasa, Didin Hikmah; Purwanto, Setiyo; Dhyan Parasakti, Ryani; Soelton, Mochamad; Arief, Harefan (Universitas Mercu Buana, 2024)
Objective: The objective of this research is to evaluate and analyze the impact of effective good corporate governance and knowledge management on organizational citizenship behavior. In addition, this research also investigated the mediating role of job satisfaction.Methodology: This research involved the saturated sample of 179 employees. Quantitative analysis was carried out through a survey approach using questionnaires and the Smart-PLS model structural analysis method.Findings: An interesting finding in this research is that consistent and structured implementation of GCG has been able to improve organizational performance by reaching the right people through the right channels in a short time. Therefore, employee job satisfaction is no longer the dominant factor in this research.Conclusion: Organizational citizenship behavior has a positive influence on Good Corporate Governance and knowledge management. The implementation of good corporate governance and well-functioning knowledge management makes a positive contribution to the level of job satisfaction. Even though job satisfaction has a significant positive impact on Organizational Citizenship Behavior, job satisfaction does not act as an intermediary in the relationship between Good Corporate Governance and Organizational Citizenship Behavior. In contrast, in the knowledge management framework, job satisfaction plays a role as a mediator that connects the influence of knowledge management on organizational citizenship behavior.